2021
DOI: 10.3390/separations8080110
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Capillary Electrophoresis for Analysis of Extracellular Vesicles (EVqCE)

Abstract: Extracellular Vesicles (EVs) gained significant interest within the last decade as a new source of biomarkers for the early detection of diseases and a promising tool for therapeutic applications. In this work, we present Extracellular Vesicles Quantitative Capillary Electrophoresis (EVqCE) to measure an average mass of RNA in EVs, determine EV concentrations and the degree of EV degradation after sample handling. We used EVqCE to analyze EVs isolated from conditioned media of three cancer cell lines. EVqCE em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The CE-LIF method enabled quantitation of RNA released from vesicles and indirect determination of EVs content in isolates obtained from cells cultures media. The authors pointed out that their method is not able to distinguish populations of EVs and requires knowledge on average RNA content in certain vesicles [21]. In our recent work, we have shown that the CE is suitable for the detection of EVs that transport green fluorescent protein (GFP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CE-LIF method enabled quantitation of RNA released from vesicles and indirect determination of EVs content in isolates obtained from cells cultures media. The authors pointed out that their method is not able to distinguish populations of EVs and requires knowledge on average RNA content in certain vesicles [21]. In our recent work, we have shown that the CE is suitable for the detection of EVs that transport green fluorescent protein (GFP).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the application of fluorescent probes in the referred works provided high selectivity towards EVs. On the other hand, CE-LIF analysis of such samples does not provide information on other components of the isolate, such as impurities [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%